Adsorption of the Polymer on a Clay Matrix : Theoretical Study - Hachem, El-Kaber; Belghazdis, Mohammed; Bendouch, Atman (International Journal of Integrated Engineering, 2022)
Adsorption of polymers is a phenomenon of great importance in a number of areas of our daily life. However, understanding this phenomenon is essential. In the present work, we are interested in the theoretical study of the adsorption phenomenon of the polymer on the sheets of a clay matrix. We have presented the different adsorption regimes encountered as well as the expressions of the surface coverage rate as a function of the volume fraction of monomer for each case. A strong adsorption was noted for the first two regimes (diluted on the surface, and semi-diluted two-dimensional on the surface) confirmed by the exponential term, and when the surface is saturated we meet the plateau regime for which the adsorption varies so logarithmic due to the occupation of most of the sites available on the surface of the clay. Finally, we presented the variation of the volume fraction as a function of z (axis perpendicular to the surface), which helps to estimate the thickness of the layer adsorbed on the surface.